Physical activity and corporeity in students of the Universidad Nacional Mayor de San Marcos - Corvetto Castro, Giovanni (2020)
The research we present is entitled: Physical activity in students of the Universidad Nacional Mayor de San Marcos is a scientific work that aspires with its results to know about corporeity in its expression related to physical-sporting activity, we believe that the human being performs physical activity due to various factors, they are not only directed to energy expenditure to ward off or prevent non-communicable diseases, such as diabetes, hypertension or obesity, but there are also factors in our corporeal being that are not only functional and mechanical; Some have to do with the motivation, emotions and social, cultural and economic characteristics by which our students develop, the contributions in this thesis can contribute to improving or designing programs to promote healthy lifestyle habits where the practice of activity Structured physical-sports and the development of a socio-critical awareness towards our health are considered essential in the university curricula, as well as in an extra-curricular way through the programs of promotion of physical-sports activity, which we mentioned before, with the altruistic purpose of improving the quality of life of people.